Secure Random 2D Subspace Techniques In GMM Based Speaker Verification System - Chong, Lee Ying (2008)
Several subspace methods are studied in Gaussian Mixture Model (GMM) based speaker verification. The objective is to reduce the dimension of feature set while retaining the prominent spectral features that can uniquely represent a user .